Competências hard e soft skills para gestão de projetos logísticos outbound baseados em modelos de maturidade - Daneluci, Gilmar de Carvalho (2021)
The logistics market is strategic for a country, exerting great influence on the economy and for companies, it is also the means to generate value for customers and shareholders. In a social scenario accelerated by digital transformation and the pandemic, outbund logistics have become increasingly present in our lives. One of the consequences of all this change is the complexity of managing projects that demand new skills, or even those that are old, but need adaptation. It is also noted that maturity models in project management have been gaining notoriety, and efforts are increasingly made to develop organizational skills in this area. In this context, we aim, with this research, to describe the hard skills and soft skills needed to work efficiently in outbound logistics projects, based on maturity models. Therefore, this study adopts, to achieve this objective, a qualitative research approach of descriptive exploratory character with the use of multiple cases, through in-depth interviews with professionals with more than five years of experience, and who are active in management outbound logistics projects. Two systematic literature reviews were also carried out, the first to explore the theme and the problem, and the second to understand the hard skill and soft skills described in the maturity models, and to compare with the current scenario of companies. In the interviews, it was identified that companies demand hard skill skills and soft skills that make up a strategy to achieve their goals. There are signs, therefore, that maturity in outbound logistics project management can contribute to the generation of competitive advantages. The results point to seven competences that come from maturity models in logistic projects. In addition, the research explores the competences in the literature within the maturity models and compares them with the competences of people involved in outbound logistics projects, as well as generating important information for professionals in this area. Thus, this research contributes from the moment it shares information to understand the necessary skills and providing important inputs for professionals working in the management of outbound logistics projects. Another contribution refers to the discovery of a new competence in outbound logistics projects, which is not included in the studied logistics maturity models.